The Visual Agnosias and Related Disorders. Issue 3 (September 2018) - Haque, Sameen; Vaphiades, Michael S.; Lueck, Christian J.
Abstract : Background: There are many disorders of higher visual processing that result from damage to specific areas of the cerebral cortex that have a specific role in processing certain aspects (modalities) of vision. These can be grouped into those that affect the ventral, or "what?", pathway (e.g., object agnosia, cerebral achromatopsia, prosopagnosia, topographagnosia, and pure alexia), and those that affect the dorsal, or "where?", pathway (e.g., akinetopsia, simultanagnosia, and optic ataxia). Evidence Acquisition: This article reviews pertinent literature, concentrating on recent developments in basic science research and studies of individual patients. Results: An overview of the current understanding of higher cerebral visual processing is followed by a discussion of the various disorders listed above. Conclusions: There has been considerable progress in the understanding of how the extrastriate visual cortex is organized, specifically in relation to functionally specialized visual areas. This permits a better understanding of the individual visual agnosias resulting from damage to these areas. Abstract : Supplemental Digital Content is Available in the Text.